Analisis Strategi Pemasaran dalam Upaya Meningkatkan Penjualan Ikan Salai Patin Pada Kelompok XYZ Analysis Strategy Marketing in an Effort to Increase Sales Salai Patin Fish at XYZ Group - Diniaty, Dewi; Kusumanto, Ismu; Roza, Fitria; Husna, Fadhillah Dinatul; Hartati, Misra; Nofirza, Nofirza (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
XYZ Group in running business have been several problems that is in the  marketing of products not yet doing activity promotions, weakening the number of requests, well as the quality of a product produced less good. This research aims to obtain the weighting of every factor which are under consideration, to know the position of the company, and provide suggestions for marketing strategies that can did be company. The see problems happen, we need marketing strategies by using the method Analytical Hie-rarchy Proses (AHP) and Strength, Weakness, Opportunity, Threat (SWOT). Based on weighting 7P using method AHP obtained product weight  as much as 12.44%, promotion of 17.90%, price of 9.93%, place of 15.82%, people of 15.63%, process of 13.45%, and physical evidence of 14, 83%. In matrix SWOT known kuadran-III the company are in a meeting between IFAS at the point -0,05 and EFAS at the point 0,49. It means , the company had a great opportunity that the market high, but still have obstacles where which is still using a simple production equipment. Alternative strategy that can be carried out is to ensure the quality of the product, increase production facilities, improve the distribution of the product, and make use of the printed media and sosial media for promotion activity